Does Firm Size Matter? An Empirical Study of Firm Performance in Indonesia - Prasetyantoko, A.; Parmono, Rachmadi (International Research Journal of Business Studies, 2009)
This study seeks to understand the relationship between firm size and performance of listed companies in Indonesia during the boom and the bust period. The result shows that generally firm size gives a positive impact to firm profitability. There is significant relationship between firm size and performance during post-crisis period. Firm size is an important factor in recovering process. Nevertheless firm size does not affect the firm market value. By employing panel data analysis of 238 listed companies in Indonesia Stock Exchange (IDX) in the period of 1994–2004, the study shows that institutional factors matter on the firm performance, based on the fact that firm with majority foreign ownership have much higher performance in both measurements, namely, return on asset (ROA) and market capitalization growth.